Treinamento funcional utilizado como forma complementar ao treinamento técnico tático em jovens jogadores de futebol - Marques Neto, Dermival Ribeiro (2022)
The objective of this study was to compare the effects of speed-oriented TF (VOTF) and strength-oriented TF (SOTF) in different parameters of COD, jumping ability, and linear speed in under-20 soccer players. For this, a quasiexperimental study was carried out in the pre-season period, lasting six weeks. 22 under-20 players were randomized into two groups: speed-oriented functional training (VOFT) and strength-oriented functional training (SOFT). Participants were evaluated pre- (week one) and post-intervention (week six) in the right-side and left-side L running test to assess fast COD (≤ 90°) and in the running test. zigzag to assess COD strength (> 90°). Jump height was measured by the countermovement jump (CMJ) used to assess elastic strength and by the squat jump (SJ) used to assess concentric strength. The maximum speed was evaluated by the sprint test in 20 meters. The turn-of-turn deficit index (COD deficit) was calculated for all COD tests. Both groups showed significant improvement over time in the L-run test for the right side (VOFT - pre: 4.09 ± 0.16 s; post: 3.88 ± 0.10 s; p = 0.004; g = 1.29); (SOFT pre: 4.07 ± 0.07 s; post: 3.80 ± 0.13 s; p < 0.001; g = 2.40). As for the zigzag test (VOFT - pre: 5.89 ± 0.14 s; post: 5.65 ± 0.25 s; p = 0.002; g = 0.98); SOFT (pre: 5.84 ± 0.10 s; post: 5.59 ± 0.17; p<0.001; g = 1.65). The COD deficit of running in L for the right side also differed significantly for VOFT (pre: 1.09 ± 0.12s; post: 0.88 ± 0.12 s; p = 0.006; g = 1.40) and for SOFT (pre: 1.12 ± 0.06 s; post: 0.83 ± 0.09; p<0.001; g = 3.44). The 20-meter sprint test, the left-side L-run test, and the left-side L-run deficit COD did not differ significantly for either group at any time point. Despite not showing a statistically significant difference over time, CMJ had a small effect size for VOFT (pre: 37.54 ± 4.56 cm; post: 39.59 ± 2.16 cm; p = 0.10; g= 0.49) and SOFT (pre: 40.14 ± 4.14 cm; post: 41.19 ± 3.10; p = 0.29; g= 0.26). While SJ had a moderate effect size for VOFT (pre 35.87 ± 3.74 cm; post: 38.50 ± 3.57 cm; p = 0.07; g = 0.58) and small for SOFT (pre: 38.35 ± 3.73; post: 39.98 ± 2.17; p = 0.16; g = 0.49). In addition, there was no significant difference between groups for any variable. Therefore, it is concluded that the application of TF protocols oriented to speed or strength as a complement to technical tactical training (TTT), over four weeks, promotes significant changes in different COD running parameters in under-20 soccer athletes.